On yantras in Early Śaiva Tantras - Csaba Kiss (Ksiegarnia Akademicka Publishing, 2021)
The term yantra is used differently in early Śaiva tantras from what we see later. In early texts, its range of meaning is wider, and it does not inevitably and typically involve objects with geometric patterns. After examining some passages from the Brahmayāmala and other mainly unpublished and/or untranslated Śaiva texts, this article makes an attempt at outlining the early history of the term. Initially, yantra seems to refer to special techniques, rituals, to attain religious goals. Later it appears to denote complex rituals of black magic involving fire-offerings with transgressive substances, using objects such as figurines embodying the targeted person, and employing mantra-inscribed materials such as birch-bark. The commonly known usage of the term yantra as a magical diagram with geometrical designs seems to have emerged only gradually.